Cross-Platform Analysis of Mammography Narratives: A Comparative Study on Social Media Engagement - Thomas Stirrat; Jonathan Garner; Parth Tailor; Daniel Weitz; Muhammad Umair; Yusuf T. Akpolat (Journal of Patient-Centered Research and Reviews)
Purpose: This study examines the representation of mammography on social media platforms, specifically, X (Twitter), Facebook, TikTok, and Instagram, from 2006 to 2023. X (Twitter) went public in 2006, Facebook in 2004, Instagram in 2012, and TikTok in 2018 (after merging with Musical.ly). The analysis starts from after the public launch years to analyze personal experiences shared online.